In-Service Training Needs of Teachers Working in Primary Schools About Mathematics: An Example in İstanbul, - Korkmaz, M., Yücel, A. S., Cesim, D. T., Gümüşdağ, H., Kılıç, B., (My University, 2014)
Background: One of the fields with changes and developments is education, for sure. Changes and developments occur in many subjects such as instruction programs, teaching techniques and methods, educational technologies etc. It is also important for teachers, playing an important role in increasing the quality and efficiency in education, to have today’s current knowledge and skills. In this sense, in-service training plays the key role. Objective: The purpose of the study is to determine the in-service training perception of the teachers working in primary schools of MEB (Ministry of Education) about mathematics, and to ascertain the level of participation. Target population of the study is Istanbul, and the sample is composed of randomly selected 238 primary schools in different regions of the city. The study is a field application. Survey method was used in obtaining data. A questionnaire was applied to the participants in order to determine their demographic characteristics and their perceptions about in-service training. Cronbach’s alpha analysis was conducted for the reliability of the questions prepared, and the 0.972 coefficient was found. Descriptive statistics, independent sample t-test, variance analysis, chi-square analysis were used in the analysis of data. Results: Following the research, differences occurred regarding some items between the opinions about in-service training by the variables of sex, education and age. Moreover, following the analysis of the items by the type of school, it has been observed to result in differences on the items like increasing activities to establish the relation between mathematics and other disciplines, developing prediction strategies of students etc. Conclusion: As a result, efforts should be exerted to determine in-service training perceptions of teachers for math class, and to organize the required activities and arrangements in this direction, and to provide participation of teachers to regular and comprehensive in-service training activities. It can be stated that in-service training received for the branch shall make positive contributions for the lesson.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Mathematics; Teachers; Primary School; In-Service Training